A MODEL SUGGESTION FOR ACTIVITY BASED COSTING IN THE ERP SYSTEM - Pazarceviren, Selim Yuksel; Ozsuer, Ugur (European Scientific Journal, ESJ, 2015)
Activity Based Costing (ABC), hase been developed as a result of the necessity that companies have been required to focus on the cost basis more closely to be able to survive and be successful in today’s competition environment. Since overhead costs are traditionally exempted from the cost analysis, they have been treated as expenses for the period. As a result of the increase in these fixed costs, it has become more important to assign overhead costs to products via a logical model. We aim to illustrate a case for an activity center to explain our model. Our model has been used in many organizations in Turkey and its success has been proved for years. We classified costs in four categories as resource costs on the basis of the volume of activities, resource costs on the basis of activity level, resource costs independent from the volume of activities, and direct resource cost. This approach lets us manage costs of activities according to their characteristics.